A Candidate-Identification Questionnaire for Patients with Postmenopausal Osteoporosis Switched from Treatment with a Daily or Weekly Bisphosphonate to Once-Monthly Ibandronate - Kutsal, Y. Gokce; Eskiyurt, N.; Irdesel, J.; Sepici, V.; Ugurlu, H.; Kirazli, Y.; Cerrahoglu, L. (Elsevier Science Inc, 2011)
…
3rd Joint Meeting of the European-Calcified-Tissue-Society/International-Bone-and-Mineral-Society -- MAY 07-11, 2011 -- Athens, GREECE